Interferometry and synthesis in radio astronomy - Thompson, A.R. (Anthony Richard) 1931- (John Wiley & Sons, 2001)
Comprehensive, authoritative coverage of interferometric techniques for radio astronomy In this Second Edition of Interferometry and Synthesis in Radio Astronomy, three leading figures in the development of large imaging arrays, including very--long--baseline interferometry (VLBI), describe and explain the technology that provides images of the universe with an angular resolution as fine as 1/20,000 of an arcsecond. This comprehensive volume begins with a historical review followed by detailed coverage of the theory of interferometry and synthesis imaging, analysis of interferometer response, geometrical relationships, polarimetry, antennas, and arrays.